INSTITUTE OF UNIVERSITY: PAST, PRESENT, FUTURE - Hnativ, Zoriana (Educological discourse, 2019)
In this article the question of the phenomenon of the environment, the intellectual center, in which the development and training of individuals and society for change is taking place, is the university institute. The Institute - as an organized system of social roles, which is a permanent and significant element of society and focuses on the basic needs and functions of the person. The models of the university are covered in historical retrospect, in particular the model of the research university of V. Humboldt, Napoleonic and Newman. The views of scientists on the model of university education with the prospect of finding conditions and promoting their implementation for the sake of the successful activity of the modern university in the new century of knowledge are considered. The emphasis is placed on the importance of the humanitarian component of education, the restriction of which will lead to irreversible consequences in the future development of society. There are many educational problems in Ukraine related to the prospects of building a world-class university. However, the current scientific potential of leading specialists in the process of reforming university education is making a great effort to bring higher education in line with modern world standards. University education is a specific cultural and social practice. Understanding the traditions and modern civilizational challenges gives you an understanding of finding the best opportunities to balance the successful design, managing your life, welfare, vision of what we can do, what schools, higher schools, education can do, in order to combine the heart and mind with the formation of a society of happy people.